GE_GERICHTE P/16143/2025 et PS/60/2025 vom 21. August 2025 - GE Cour de justice (2025)
RÉCUSATION;CURATELLE;ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;ABUS D'AUTORITÉ;ASSISTANCE JUDICIAIRE | CPP.58; CPP.106; CC.16; CPP.310; CPP.56.letf; CP.312; CPP.132